Afinal, fruímos e problematizamos a ginástica de conscientização corporal da escola? - Melo, Adauto André Soares (2024)
According to the National Common Curricular Base - BNCC, Physical Education is a curricular component belonging to the Language area, composed of themes that are called thematic units: Plays and Games, Sports, Gymnastics, Dances, Fights and Adventure Body Practices. This work focused on the thematic unit Gymnastics and the object of knowledge Body Awareness Gymnastics (GCC). To structure this thematic unit, according to the BNCC, it is organized into three segments: General Gymnastics, Physical Conditioning Gymnastics and Body Awareness Gymnastics. Using the GCC guiding axis, which can be revealed through breathing, postural issues and full attention to oneself, we seek together with the students to select a proposal that is feasible to our reality and in the interest of research collaborators so that they can exercise engagement and protagonism in Physical Education classes. Thus, the objective of the research was to investigate how the construction, based on the gymnastics thematic unit, and the GCC object of knowledge, with students in the 9th year of Elementary School, classes that promote body awareness as a possibility of experience. The research had a qualitative approach and took place at the Jayme Veríssimo de Campos Júnior State School, in the municipality of Alta Floresta, MT, with 21 (twenty-one) students from a 9th grade class as subjects, being inspired by the methodological path of the research-action. As a data collection instrument, two questionnaires were used, one for entry, to find out what the participants knew about the topic and, based on this diagnostic instrument, an intervention plan was created, building a didactic unit for teaching this category of gymnastics. At the end of the didactic unit, an exit questionnaire was administered to understand the effectiveness of the proposal in achieving an expanded awareness of gymnastics. Another instrument for data collection adopted in this study was the field journal, so that we could observe the collaborator’s relationship with class interventions. All data collected was analyzed empirically and was organized and related in light of the theories studied, using as a reference the analysis of the coding categories proposed by Minayo. We concluded that the gymnastics thematic unit and the object of knowledge Body Awareness Gymnastics demonstrated a practice (Conceptual, Procedural and Attitudinal) possible in Physical Education classes for ninth grade students, as it promoted body awareness and perception of themes of movement body culture.